Neural markers and implantable bioelectronic systems for the treatment of hypertension. Issue 2 (25th May 2018) - Sevcencu, Cristian; Struijk, Johannes J
Present bioelectronic devices for the treatment of resistant hypertension are based on electric stimulation of the carotid baroreceptors. Left vagus nerve (LVN) stimulation, to modulate the aortic baroreceptor signals has received less attention. Undeservedly so, since the aortic baroreceptors have a central role in the blood pressure (BP) control. Moreover, from the same site at the LVN where the stimulation is applied, a nerve signal can be recorded as well. This nerve signal mimics the BP in the aortic arch and mirrors the respiratory activity. As such, this signal could be used in a closed-loop LVN stimulation system to monitor the BP and physical activity as needed for safety and efficacy of any BP control system.